A multiplex PCR assay for the differentiation of Mycobacterium tuberculosis complex reveals high rates of mixed-lineage tuberculosis infections among patients in Ghana - Owusu, Wellington; van Vliet, Arnoud H. M.; Riddell, Natalie E.; Stewart, Graham; Akwani, Winifred C.; Aryeetey, Sherihane; Arthur, Rejoice Agyeiwaa; Sylverken, Augustina Angelina; Hingley-Wilson, Suzanne M. (Frontiers in Cellular and Infection Microbiology, 2023)
In low-resource settings with high tuberculosis (TB) burdens, lack of rapid diagnostic methods for detection and differentiation of Mycobacterium tuberculosis complex (MTBC) is a major challenge affecting TB management. This study utilized comparative genomic analyses of MTBC lineages; M. tuberculosis, M. africanum Lineages 5/6 and M. bovis to identify lineage-specific genes. Primers were designed for the development of a Multiplex PCR assay which was successful in differentiating the MTBC lineages. There was no cross-reaction with other respiratory pathogens tested. Validation of the assay using clinical samples was performed with sputum DNA extracts from 341 clinically confirmed active TB patients. It was observed that 24.9% of cases were caused by M. tuberculosis, while M. africanum L5 & L6 reported 9.0% and 14.4%, respectively. M. bovis infection was the least frequently detected lineage with 1.8%. Also, 27.0% and 17.0% of the cases were PCR negative and unspeciated, respectively. However, mixed-lineage TB infections were recorded at a surprising 5.9%. This multiplex PCR assay will allow speciation of MTBC lineages in low-resource regions, providing rapid differentiation of TB infections to select appropriate medication at the earliest possible time point. It will also be useful in epidemiological surveillance studies providing reliable information on the prevalence of TB lineages as well as identifying difficult to treat cases of mixed-lineage tuberculosis infections.